A review of underwater acoustic metamaterials for underwater acoustic equipment - Zhu, Zhenjing; Hu, Ning; Wu, Junyi; Li, Wenxin; Zhao, Jiabao; Wang, Maofa; Zeng, Fanzong; Dai, Huajie; Zheng, Yongju (Frontiers in Physics, 2022)
Researchers use underwater acoustic equipment to explore the unknown ocean environment, which is one of the important means to understand and utilize the ocean. For underwater acoustic equipment, the application of underwater acoustic metamaterials is the premise to ensure and improve the performance of underwater acoustic communication, acoustic stealth, and sonar detection. Due to the limitations of mass density law and high hydrostatic pressure, traditional underwater acoustic materials cannot effectively absorb low-frequency sound waves and have low efficiency of elastic energy conversion. The sound absorption effect is poor under low frequency and high hydrostatic pressure. In recent years, with the development of acoustic metamaterials technology, all kinds of underwater acoustic metamaterials have also been proposed. Compared with sound waves propagating in the air, underwater sound is more difficult to control than air sound with the same frequency, so the design of underwater acoustic metamaterials is more complicated. This paper reviews the basic characteristics, development history of sound absorption, sound insulation decoupling, and underwater acoustic guided metamaterials, then the existing problems and the future development direction of underwater acoustic metamaterials are discussed.